Trace the polymerization induced by gamma-ray irradiated silica particles. (August 2016) - Lee, Hoik; Ryu, Jungju; Kim, Myungwoong; Im, Seung Soon; Kim, Ick Soo; Sohn, Daewon
Abstract: A γ-ray irradiation to inorganic particles is a promising technique for preparation of organic/inorganic composites as it offers a number of advantages such as an additive-free polymerizations conducted under mild conditions, avoiding undesired damage to organic components in the composites. Herein, we demonstrated a step-wise formation mechanism of organic/inorganic nanocomposite hydrogel in detail. The γ-ray irradiation to silica particles dispersed in water generates peroxide groups on their surface, enabling surface-initiated polymerization of acrylic acid from the inorganic material. As a result, poly(acrylic acid) (PAA) covers the silica particles in the form of a core-shell at the initial stage. Then, PAA-coated silica particles associate with each other by combination of radicals at the end of chains on different particles, leading to micro-gel domains. Finally, the micro-gels are further associated with each other to form a 3D network structure. We investigated this mechanism using dynamic light scattering (DLS) and transmission electron microscopy (TEM). Our result strongly suggests that controlling reaction time is critical to achieve specific and desirable organic/inorganic nanocomposite structure among core-shell particles, micro-gels and 3D network bulk hydrogel. Highlights: Pre-irradiation of γ-ray enables an effective synthesis of polymer/inorganic nanocomposites toward pre-selected properties. Solution dynamics and electron microscopic studies reveal the formation mechanism of the nanocomposites. Reaction time is a critical parameter to achieve desirable organic/inorganic nanocomposite structure in a given system.